Comparison of three α‐glucosidase inhibitors for glycemic control and bodyweight reduction in Japanese patients with obese type 2 diabetes. Issue 2 (25th October 2013) - Sugihara, Hitoshi; Nagao, Mototsugu; Harada, Taro; Nakajima, Yasushi; Tanimura‐Inagaki, Kyoko; Okajima, Fumitaka; Tamura, Hideki; Inazawa, Takeshi; Otonari, Takatoshi; Kawakami, Masanobu; Oikawa, Shinichi
Abstract Aims/Introduction α‐Glucosidase inhibitors (αGIs) are widely used for the primary treatment of type 2 diabetes. We compared the clinical effects of three αGIs (miglitol, acarbose and voglibose) in patients with obese type 2 diabetes. Materials and Methods Japanese patients (n = 81) with obese type 2 diabetes (body mass index [BMI] ≥25 kg/m2) were enrolled in this multicenter, open‐label study. The participants were randomized into the miglitol (n = 18), acarbose (n = 22), voglibose (n = 19) or control (n = 22) groups. Glycemic control (fasting blood glucose and glycated hemoglobin [HbA1c]), bodyweight, BMI, serum insulin, serum lipids (low‐density lipoprotein and high‐density lipoprotein cholesterol, and triacylglycerols) and adipocytokines (leptin and adiponectin) were evaluated every 4 weeks for 12 weeks. Results In the miglitol group, HbA1c was improved significantly from the baseline at all points. The changes in HbA1c at 8 and 12 weeks from baseline were greater in the miglitol group than the control group. The voglibose group showed significant improvements in HbA1c at 12 weeks. Bodyweight and BMI were decreased significantly in the miglitol group. In addition, significant correlations were observed between the decrements in HbA1c and bodyweights over 12 weeks in the miglitol (r = 0.759, P < 0.001) and voglibose groups (r = 0.667, P = 0.002). Serum lipid and adipocytokine levels were not altered in any groups. Conclusions αGIs, especially miglitol, can effectively control blood glucose and bodyweight in obese type 2 diabetes. This study was registered with UMIN (no. UMIN000006465).